Kebijakan Perlindungan Hak Pendidikan â€œAnakâ€ Dalam Proses Peradilan Pidana Di Lembaga Pembinaan Khusus Anak - Wulandari, Sri (SPEKTRUM HUKUM, 2025)
The Indonesian criminal justice system has undergone significant changes since the enactment of Law Number 11 of 2012, which focuses on the protection of children's educational rights. This study analyzes the policy issue of protecting children's education in the criminal justice process and the implementation of children's rights in the Special Children's Development Institution (LPKA). The study uses normative juridical research to examine the policy protection of children's educational rights in the criminal justice process. Law No. 22 of 2022 focuses on children aged 12-18 suspected of committing criminal acts. These children often face stigmatization and discrimination, necessitating legal protection, such as diversion and restorative justice. The study emphasizes the importance of treating children differently from adult criminal offenders and prioritizing their best interests. The transition from Correctional Institutions to LPKA demonstrates the state's commitment to protecting and respecting children's rights, providing facilities and infrastructure for formal and non-formal education during criminal proceedings.